Hunting game - Tursten, Helene, 1954- (Tursten, Helene, 1954- Embla Nyström investigations, 2019)
"The first installment in Helene Tursten's brand new series featuring the strong, smart Detective Inspector Embla Nystrom. From a young age, 28-year-old Embla Nystrom has been plagued by chronic nightmares and racing thoughts. Though she still develops unhealthy fixations and makes rash decisions from time to time, she has learned to channel most of her anxious energy into her position as Detective Inspector in the mobile unit in Gothenburg, Sweden, and into sports. A talented hunter and prize-winning Nordic welterweight, she is glad to be taking a vacation from her high-stress job to attend the annual moose hunt with her family and friends. But when Embla arrives at her uncle's cabin in rural Dalsland, she sees an unfamiliar face has joined the group: Peter, an enigmatic young divorce. And she isn't the only one to take notice. One longtime member of the hunt doesn't welcome the presence of an outsider and is quick to point out that with Peter, the group's number reaches thirteen, a bad omen for the week. Sure enough, a string of unsettling incidents follow, culminating in the disappearance of two men from a neighboring group of hunters. Embla takes charge of the search, and they soon find one of the missing men floating facedown in the nearby lake, his arm tightly wedged between two rocks. Just what she needs on her vacation. With the help of local reinforcements, Embla delves into the dark pasts of her fellow hunters in search of a killer"--